Pengaruh Personality Traits terhadap Perencanaan Keuangan Keluarga - -, Subiaktono (JDM (Jurnal Dinamika Manajemen), 2013)
The aim of this research is to examine and analyze the effect of personality traits that consists of agreeableness, conscientiousness, body focus, materialism and need for arousal on the family financial planning. The sample of this research is a group of people who are employees of the BTN Bank Semarang branch with qualitative and quantitative analysis tools. The result shows that independent variables (agreeableness, conscientiousness, body focus, materialism and need for arousal) have significant effects on the family financial planning.It could be concluded that the lack of employee ability in how to manage family finance is caused by their own knowledge and their psychological factor. Psychological factor is often considered as a key factor in family financial management decision making process. The stronger personality aspect of husband and wife as the financial manager, the greater effects will occur on psychological decision to the financial decision. Lifestyle, unplanned shopping pattern, non-budgeted social expenses, environment, and financial management literacy become the supporting factors that cause a bad management or even a failure.